The Influence of Leadership and the Implementation of Occupational Safety and Health (OSH) on the Performance of Construction Employees - Putri Az Zahra, Ghefi Amellia; Rini, Hesty Prima (Management Science Research Journal, 2025)
The intensifying nature of business competition compels organizations to enhance employee performance through effective leadership and the systematic implementation of occupational safety and health (OSH) practices. This research aims to examine the impact of leadership and OSH implementation on the performance of field construction employees at CV. XYZ. A quantitative research design was adopted, with data collected using a five-point Likert-scale questionnaire. The study involved a population and sample comprising all 42 field construction employees of CV. XYZ, selected through a saturated sampling technique. Data were analyzed using (PLS-SEM) technique, supported by the SmartPLS software. The study reveal that both leadership and OSH implementation exert a positive and significant influence on employee performance. These results underscore that effective leadership and consistent adherence to OSH practices are crucial in enhancing the performance of field construction employees.